DISCOVERY AND DEVELOPMENT OF IULTINSKOYE TIN-TUNGSTEN DEPOSIT - V. V. Romanova (Известия высших учебных заведений: Геология и разведка, 2018)
The Iultinskoye deposit was discovered 80 years ago in the remote and unexplored region of Chukotka. Discovery and development of the deposit were accompanied by serious difficulties. A brief biographic data about the discoverer of the deposit V.N. Milyaev has been presented here. The Iultinsky mining processing plant, which was opened in 1959, was closed in 1994 due to the changing in the economic situation. The deposit was conserved, Iultinsky village was liquidated. Vernadsky State Geological Museum RAS has samples of cassiterite and wolframite, collected by geologists of the Second Chukotka Glavsevmorput expedition in the year of the deposit discovery.